The impact of social influence on adolescent intention to smoke: Combining types and referents of influence - Vitória, P.; Salgueiro, M.F.; Silva, S.A.; De Vries, H. (British Journal of Health Psychology, 2009)
Objectives. Theory and research suggest that the intention to smoke is the main determinant of smoking initiation and emphasizes the role of cognitive and social factors on the prediction of the intention to smoke. However, extended models such as the I-Change and results from published studies reveal inconsistencies regarding the impact of social influence on the intention to smoke. Possible explanations for this may be the definition and measurement of the constructs that have been used. Design and methods. The current study was designed with two main goals: (i) to test a measurement model for social influence, combining different types of social influence (subjective norms, perceived behaviour, and direct pressure) with various referents of influence (parents, siblings, peers, and teachers); (ii) to investigate the impact of social influence on adolescent intention to smoke, controlling for smoking behaviour. LISREL was used to test these models. The sample includes 3,064 Portuguese adolescents, with a mean age of 13.5 years, at the beginning of the seventh school grade. Results. The hypothesized measurement model of social influence was supported by results and explained 29% of the variance of the intention to smoke. A more extended model, including attitude and self-efficacy, explained 55% of the variance of the intention to smoke. Perceived behaviour of peers, parental norms, and perceived behaviour of parents were the social influence factors with impact on adolescent intention to smoke. Conclusions. Results suggest that different referents exert their influence through distinct types of social influence and recommend further work on the definition and measurement of social influence.